Influence of Early Low‐Temperature and Later High‐Temperature Diagenesis on Magnetic Mineral Assemblages in Marine Sediments From the Nankai Trough. (23rd October 2021) - Kars, Myriam; Köster, Male; Henkel, Susann; Stein, Rüdiger; Schubotz, Florence; Zhao, Xiang; Bowden, Stephen A.; Roberts, Andrew P.; Kodama, Kazuto
Abstract: Diagenesis can have a major impact on sedimentary mineralogy. Primary magnetic mineral assemblages can be modified significantly by dissolution or by formation of new magnetic minerals during early or late diagenesis. At International Ocean Discovery Program Site C0023, which was drilled in the protothrust zone of the Nankai Trough during Expedition 370, offshore of Shikoku Island, Japan, non‐steady state conditions have produced a complex sequence of magnetic overprints. Detailed rock magnetic measurements, which characterize magnetic mineral assemblages in terms of abundance, grain size, and composition, were conducted to assess magnetic mineral alteration and diagenetic overprinting. Four magnetic zones (MZs) are identified down‐core from ∼200 to 1, 100 m below sea floor based on rock magnetic variations. MZ 1 is a high magnetic intensity zone that contains ferrimagnetic greigite, which formed at shallow depths and is preserved because of rapid sedimentation. MZs 2 and 4 are low magnetic intensity zones with fewer magnetic minerals, mainly coarse‐grained (titano‐)magnetite and hematite. This magnetic mineral assemblage is a remnant of a more complex assemblage that was altered diagenetically a few million years after deposition when the site entered the Nankai Trough. MZ 3 is a high magnetic intensity zone between MZs 2 and 4. It contains authigenic single‐domain magnetic particles that probably formed from fluids that circulated through faults in the accretionary prism. Varying sediment supply and organic matter input through time, burial temperature, and tectonic fluid circulation are the primary drivers of magnetic mineral assemblage variations. Key Points: Four down‐core diagenetic zones are identified with magnetic mineral assemblages reflecting sediment provenance and diagenetic processes Limited exposure of sediments to dissolved sulfide due to rapid burial leads to greigite preservation in the upper ∼460 m High‐temperature diagenetic processes are responsible for later iron oxide formation and reduction in deeper sediments